The pharmaceutical supply of brand and generic medicines in different rural and urban areas of Egypt. - Afify, Yasin M. Ragaey (AUC Knowledge Fountain, 2016)
Medicines are an important intervention for protecting public health. While medicines have brand and generic type products, those used for treating non-communicable diseases are used by patients for life. The pharmaceutical market is not a competitive market with asymmetric flow of information. Equal access to both types of medicines is part of equal access to health care in different socioeconomic areas. Patients with non-communicable diseases should own their choice of whether brand or generic medicines for their treatment not the market supply that dictates their consumption. In this thesis, we used data for availability of 39 medicines treating non-communicable diseases selected based on some inclusion criteria. Our hypothesis assumed social equity that presumes equal access to both medicine types in varying rural and urban areas where population having chronic conditions have to acquire their treatments for life. Data was modeled and logistic regression was used. Results were produced using statistical software; both SPSS and R. Primary findings show that rural and urban areas have different pattern of market supply for both brand and generic medicine types. In the same settings of a socioeconomic area, the probability of supply of brand rather than generic medicines increases by the increase in price. Social health insurance coupled by pharmaceutical Track and Trace system and combined pricing mechanisms should be in place to insure equilibrium between market supply and equal access to medicines. Patients with non-communicable diseases in different urban and rural areas in Egypt should be left to consume their medicine type at their choice. Guidelines for promotion of prescription medicines, guidelines for prescribing practices should be in place to improve the market equilibrium.